Perbandingan Dampak Alokasi Anggaran terhadap Pendapatan dalam Dua Rezim: Pilkada Langsung Versus Tidak Langsung - Heriyana, Aan; Adrison, Vid (Jurnal Kebijakan Ekonomi, 2019)
This study compares the impact of budget allocations between regions that have carried out direct regional elections and indirectly and their impact on regional per capita income. The budget allocation uses the allocation of capital expenditure and indirect expenditure on the Regional Expenditure Budget (APBD) of regencies and cities in Indonesia. Empirically, in the 2005-2010 period in Indonesia, the estimation results using Pooled Least Square did not show a significant difference in the impact of budget allocation on regional per capita income between the regime and direct versus indirect elections. But regionally there are significant differences in districts and cities in the island group of Sumatra when compared with other island groups in Indonesia, namely there are differences in the impact on the total budget that affects the per capita income where the average head of the region elected through the direct election impacts lower than indirectly selected regional heads.